Systematic review of Mandarin pronunciation learning strategies / Dr. Ting Hie Ling, Ye Jun and Lam Kai Chee - Ting, Hie Ling; Ye, Jun; Lam, Kai Chee (Universiti Teknologi MARA, Kedah, 2024)
This study utilized a systematic review approach in reviewing previous studies on Mandarin pronunciation learning strategies. Two accessible electronic databases, namely CNKI and Google Scholar were selected as the platform to search all relevant publication. A total of 14 relevant publications were collected and analysed. Findings of this study revealed that majority of MPLS publication are empirical studies covered quantitative and mixed method studies. Population selected in MPLS study involved both learners studied Mandarin in target and non-target environment. This study also indicated that cognitive and metacognitive strategies were perceived as the most frequent used strategies among Mandarin learners, while compensation strategies were the least frequently used strategies. Individual factors were major studied area compared to other factors. Findings showed that the studies on MPLS remain scarce. Hence, to fill the gap, it was highly recommended that more in-depth studies on MPLS needed to be carried out in future.